Towards greater vegetable consumption: Change the product or change the person? Case studies of two vegetable commodities. (March 2015) - Cox, David N.; Poelman, Astrid A.M.
Abstract: Objective: This study sought to understand if changing the attributes of specific vegetables would increase intention to purchase. Design: Product attributes and consumer issues that drive and inhibit the purchase and consumption of cauliflower ( Brassica oleracea var . Botrytis ) and green beans ( Phaseolus vulgaris L .) were tested using on-line nationwide conjoint studies that modelled commodity attributes (colour, communication of sensory properties, health claims, price and convenience/portion) that literature suggested might be important in influencing purchase intention. Commodities were explored as main meal and snack items. Consumers rated their intention to purchase the commodities with differing attributes. Attitudes, liking and socio-demographics were also measured to identify different groups' interests. Children's influence and liking were measured to assess their impact on purchasing decisions. Setting: Online, nationwide, Australia. Subjects: 1002 main grocery buyers 18–65 years (500 and 502 for each commodity). Results: Participants were found to prefer current offerings: white, whole, cauliflowers at lowest cost, and green beans, loose at lowest cost. Both commodities had potential as snack items. Some health claims had small positive effects. Children's liking was low, limiting purchase in three-quarters of families. Segmentation was found for cauliflower only: some participants showed interest in a heart health claim, whereas others were interested in mixed coloured floret snack packs. Conclusion: Changing cauliflower and green beans attributes has limited potential to increase demand. Rather, it is more likely that changing consumer behaviour towards vegetables is required with strategies aimed at children. Highlights: Attributes of specific vegetable commodities were experimentally manipulated. These were hypothesized to increased purchase intention. Only very limited support was found for the effects of changing attributes. Rather, addressing children's liking may be a more effective strategy.